The effect of Ag element on the microstructure characteristic evolution of an Al–Cu–Li–Mg alloy - Dan-yang Liu (Journal of Materials Research and Technology, 2020)
The influence of Ag on the microstructure evolution of an aged Al–Cu–Li–Mg alloy was studied. The coarse Cu-rich precipitates containing Ag and Mg were found during the whole ageing process of Al–Cu–Li–Mg–Ag alloy. Besides, Ag addition in the Al–Cu–Li–Mg alloy accelerates the hardness value reduction of the overaged alloy. When the alloy was over heat-treated, more coarse Cu-rich phases containing Ag and Mg are presented at the grain boundaries. These discrete coarse precipitates accelerate the hardness reduction of the overaged alloy.